Avian coronavirus isolated from a pigeon sample induced clinical disease, tracheal ciliostasis, and a high humoral response in day-old chicks - Martini, Matheus C.; Caserta, Leonardo C.; Santos, Marcia M. A. B. dos; Barnabe, Ana C. S.; Duraes-Carvalho, Ricardo; Padilla, Marina A.; Simao, Raphael M.; Rizotto, Lais S.; Simas, Paulo V. M.; Bastos, Juliana C. S.; Cardoso, Tereza C. [UNESP]; Felippe, Paulo A. N.; et al. (Taylor & Francis Ltd, 2018)
The detection of avian coronaviruses (AvCoV) in wild birds and the emergence of new AvCoV have increased in the past few years. In the present study, the pathogenicity of three AvCoV isolates was investigated in day-old chicks. One AvCoV isolated from a pigeon, which clustered with the Massachusetts vaccine serotype, and two AvCoV isolated from chickens, which grouped with a Brazilian genotype lineage, were used. Clinical signs, gross lesions, histopathological changes, ciliary activity, viral RNA detection, and serology were evaluated during 42 days post infection. All AvCoV isolates induced clinical signs, gross lesions in the trachea, moderate histopathological changes in the respiratory tract, and mild changes in other tissues. AvCoV isolated from the pigeon sample caused complete tracheal ciliostasis over a longer time span. Specific viral RNA was detected in all tissues, but the highest RNA loads were detected in the digestive tract (cloacal swabs and ileum). The highest antibody levels were also detected in the group infected with an isolate from the pigeon. These results confirm the pathogenicity of Brazilian variants, which can cause disease and induce gross lesions and histopathological changes in chickens. Our results suggest that non-Galliformes birds can also play a role in the ecology of AvCoV.
Keywords: Infectious bronchitis virus; pigeon; chicken; pathogenicity; ciliostasis